SQL:1999 understanding relational language components - Melton, Jim, 1946-; Simon, Alan R. (San Francisco, Calif. ; London : Morgan Kaufmann, 2002)
This book is the best way to make the leap from SQL-92 to SQL:1999, but it is much more than just a simple bridge between the two. The latest from celebrated SQL experts Jim Melton and Alan Simon, SQL:1999 is a comprehensive, eminently practical account of SQL's latest incarnation and a potent distillation of the details required to put it to work. Written to accommodate both novice and experienced SQL users, SQL:1999 focuses on the language's capabilities, from the basic to the advanced, and the ways that real applications take advantage of them. Throughout, the authors illustrate features and techniques with clear and often entertaining references to their own custom database, which can be downloaded from the companion Web site. * Gives authoritative coverage from an expert team that includes the editor of the SQL-92 and SQL:1999 standards. * Provides a general introduction to SQL that helps you understand its constituent parts, history, and place in the realm of computer languages. * Explains SQL:1999's more sophisticated features, including advanced value expressions, predicates, advanced SQL query expressions, and support for active databases. * Explores key issues for programmers linking applications to SQL databases. * Provides guidance on troubleshooting, internationalization, and changes anticipated in the next version of SQL. * Contains appendices devoted to database design, a complete SQL:1999 example, the standardization process, and more.
Database and technology foundations -- Introduction to SQL: 1999 -- Basic table creation and data manipulation -- Basic data definition language (DDL) -- Values, basic functions, and expressions -- Advanced value expressions : CASE, CAST, and row value expressions -- Predicates -- Working with multiple tables : the relational operators -- Advanced SQL query expressions -- Constraints, assertions, and referential integrity -- Active databases and triggers -- Accessing SQL from the real world -- Cursors -- Privileges, users, and security -- Transaction management -- Connections and remote database access -- Routines and routine invocation (functions and procedures) -- Dynamic SQL -- Call-level interface (CLI) -- Diagnostics and error management -- Internationalization aspects of SQL: 1999 -- Information schema -- A look to the future.
Includes bibliographical references and index.
Keywords: SQL (Computer program language).; Database management; Electronic books